2017
DOI: 10.1098/rsta.2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

On the hydrogen activation by frustrated Lewis pairs in the solid state: benchmark studies and theoretical insights

Abstract: Recently, the concept of small molecule activation by frustrated Lewis pairs (FLPs) has been expanded to the solid state showing a variety of interesting reactivities. Therefore, there is a need to establish a computational protocol to investigate such systems theoretically. In the present study, we selected several FLPs and applied multiple levels of theory, ranging from a semi-empirical tight-binding Hamiltonian to dispersion corrected hybrid density functionals. Their performance is benchmarked for the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…Theoretical studies showed that the gas−phase reaction energies (ΔE) are always more negative in solid state than that in both gas and solution phase for the same H2 activation reactions. 73 It is believed that the LA/LB work in a cooperated fashion, in both the formation (Figure 1). The results showed that H2 activation by tBu3P/B(C6F5)3 pair mainly consists of two elementary steps: hydride (H − ) transfer to B and proton (H + ) transfer to P, which is quite consistent with the previous AIMD studies.…”
Section: Factors Determining Reactivitymentioning
confidence: 99%
“…Theoretical studies showed that the gas−phase reaction energies (ΔE) are always more negative in solid state than that in both gas and solution phase for the same H2 activation reactions. 73 It is believed that the LA/LB work in a cooperated fashion, in both the formation (Figure 1). The results showed that H2 activation by tBu3P/B(C6F5)3 pair mainly consists of two elementary steps: hydride (H − ) transfer to B and proton (H + ) transfer to P, which is quite consistent with the previous AIMD studies.…”
Section: Factors Determining Reactivitymentioning
confidence: 99%
“…We begin with a conceptual consideration of the broader context of FLP chemistry by Fontaine & Stephan [1] and then Bullock & Chambers [2] provide an overview of the notion of FLP chemistry across the periodic table. Grimme and co-workers [3] provide a discussion of the theoretical considerations of the quintessential reaction of FLPs, the activation of H 2 , while Erker and co-workers [4] report on the development of FLPs derived from carbon-Lewis bases and boron-Lewis acids. Melen and co-workers [5] discuss reactions of FLPs inspired by biologically relevant systems and Uhl and co-workers [6] describe aluminiumphosphorus based FLPs.…”
mentioning
confidence: 99%
“…We employed a hierarchy of theoretical methods, ranging from semi-empirical tight-binding Hamiltonians to accurate London dispersion corrected hybrid density functionals. 38 45 More discussion of methodological points and computational details can be found in our previous benchmark study 46 and in the ESI. † The main representative results of the PCy 3 /B(C 6 F 5 ) 3 FLP are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%